82.3k views
0 votes
If f (x) = {(4 – 1), then what is f (2)?
f(2)=

If f (x) = {(4 – 1), then what is f (2)? f(2)=-example-1

2 Answers

3 votes

Answer:

1

Explanation:

substitute
x with 2


(1)/(2)(4-2)

subtract 2 from 4


(1)/(2) (2)

multiply
(1)/(2) by 2 or cancel the common factor

1

User Yajay
by
5.1k points
3 votes

Steps to solve:

f(x) = 1/2(4 - x) when x = 2

~Substitute

f(2) = 1/2(4 - 2)

~Subtract whats in parenthesis

f(2) = 1/2(2)

~Multiply

f(2) = 1

Best of Luck!

User ZeFrenchy
by
5.2k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.